The expanded genome of Hexamita inflata, a free-living diplomonad - Akdeniz, Zeynep; Havelka, Michal; Stoklasa, Michal; Jiménez-González, Alejandro; Žárský, Vojtěch; Xu, Feifei; Stairs, Courtney W; Jerlström-Hultqvist, Jon; Kolísko, Martin; Provazník, Jan; Svärd, Staffan; Andersson, Jan O; et al. (Scientific data, 2025)
Diplomonads are anaerobic, flagellated protists, being part of the Metamonada group of Eukaryotes. Diplomonads either live as endobionts (parasites and commensals) of animals or free-living in low-oxygen environments. Genomic information is available for parasitic diplomonads like Giardia intestinalis and Spironucleus salmonicida, while little is known about the genomic arrangements of free-living diplomonads. We have generated the first reference genome of a free-living diplomonad, Hexamita inflata. The final version of the genome assembly is fragmented (1241 contigs) but substantially larger (142 Mbp) than the parasitic diplomonad genomes (9.8-14.7 Mbp). It encodes 79,341 proteins; 29,874 have functional annotations and 49,467 are hypothetical proteins. Interspersed repeats comprise 34% of the genome (9617 Retroelements, 2676 DNA transposons). The large expansion of protein-encoding capacity and the interspersed repeats are the major reasons for the large genome size. This genome from a free-living diplomonad will be the basis for further studies of the Diplomonadida lineage and the evolution of parasitism-free living style transitions.
Keywords: rozptýlené repetitivní sekvence; genom protozoální; Diplomonadida; Retroelements; Genome, Protozoan; retroelementy; Interspersed Repetitive Sequences